Mandibular Foramen –The Peephole - Deepali P Mohite; Prakash M Mohite; Devendra Palve; Alka H Hande (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Forensic Odontology is a rapidly evolving branch of dentistry which deals with theidentification of an individual. In instances of deceased individual, establishing identity may still posedifficulties depending upon the time that has elapsed since death. The oral structures can reliably be usedfor establishing identity of the deceased as they are preserved for long after death. The mandibular foramenis amongst the core structures & has been used for age estimation with reliable degree of accuracy usingradiographs which is a non-invasive and easily reproducible technique. Hence we decided to assess itsimportance in establishing gender. Methods: Digital Orthopantomograph (OPG) were used for the study asthey are taken for all dental procedures and can be preserved as records and may facilitate comparison ofante-mortem and post-mortem records. Various dimensions from the mandibular foramen were recorded.Conclusion: We found statistically significant correlation of Anteroposterior and Posteroanterior dimensionsin position of mandibular foramen to gender.